Bio-Informed Emerging Technologies and Their Relation to the Sustainability Aims of Biomimicry. (1st October 2019) - Bensaude-Vincent, Bernadette
Synthetic biology, materials chemistry and soft robotics are fast becoming leading disciplines within the field of practices which look to nature for inspiration and opportunities. In this article I discuss how these molecular-scale practices fit within the existing trends of bio-informed design defined at the macro level, that is, bionics, biomimetics and more specifically biomimicry. Based on the metaphysical views underlying bio-informed design practices, I argue that none of them currently fit the biomimicry model, as they are not consistently concerned with environmental sustainability. While biomimetic chemistry loosely belongs to the field of biomimetics, and soft robotics to the field of bionics, both practices have a profound impact on their respective fields, as they question the places of nature and engineers.